Impact of maternal vitamin D status during pregnancy on neonatal vitamin D status - El Koumi, Mohamed A.; Ali, Yasser F.; Abd El Rahman, Rehab N. (The Turkish Journal of Pediatrics, 2013)
Maternal vitamin D deficiency is not uncommon. The lack of vitamin D during pregnancy may result in poor fetal growth and altered neonatal development that may persist into later life. Recognition of risk factors and early detection of vitamin D deficiency during pregnancy are important in order to prevent neonatal vitamin D deficiency and related complications. The aim of the current study was to assess the effect of maternal vitamin D status on the neonatal vitamin D stores. A total of 92 pregnant women at the end of the 3rd trimester and their newborns were recruited from Zagazig University Maternity and Children’s Hospital, Egypt during the year 2011. Maternal and cord blood samples were taken at the beginning of the third trimester for determination of serum levels of circulating 25-hydroxyvitamin D3 (25(OH) D3) concentration, serum calcium (Ca++), phosphorus (PO4), and alkaline phosphatase (ALP). Compared with pregnant women with adequate vitamin D levels, women deficient in vitamin D had infants with vitamin D deficiency (X±SD 33.44±18.33 nmol/L vs. 55.39±17.37 nmol/L, p=0.01). Maternal and neonatal serum 25(OH)D3 levels showed a positive correlation with serum Ca++ and negative correlation with serum PO4 and ALP. Neonatal 25(OH) D3 was related to maternal third trimester levels (r=0.89, p=0.01). The newborn serum 25(OH)D3 concentrations are reliant on maternal vitamin D status, and the poor maternal vitamin D status may adversely affect neonatal vitamin D status and consequently Ca++ homeostasis.